Child‐related attributions of hostile intent and harsh discipline: Moderating effects of anger. Issue 6 (16th August 2019) - Milner, Joel S.; Wagner, Michael F.; Crouch, Julie L.; McCarthy, Randy J.
Abstract: Two studies tested whether attributions of hostile intent (AHI) and anger for ambiguous child behaviors uniquely predict parents' harsh verbal discipline (HVD) and harsh physical discipline (HPD) or whether AHI only predicts harsh discipline when AHI occurs in conjunction with anger, as suggested by the Integrated Cognitive Model of general aggression (Wilkowski & Robinson, 2010, J. Pers., 78, 9–38). Replicating previous studies, the expected positive bivariate relationships between AHI, anger, HVD, and HPD were found in Study 1 ( N  = 493). However, when AHI, anger, and the AHI by anger interaction were considered simultaneously, patterns of prediction varied by discipline type. For HVD, high levels of AHI, high levels of anger, and the AHI by anger interaction (at high levels of AHI and anger) each were significant predictors. For HPD, low levels of AHI, high levels of anger, and the AHI by anger interaction (at high levels of AHI and anger) were significant predictors, suggesting a possible suppressor effect for AHI. These results were replicated in Study 2 ( N  = 503). Thus, there was support for the contention that AHI only predicts harsh discipline when AHI occurs in conjunction with anger with respect to HPD but this was not the case for HVD. Since AHI suppressor effects were observed for HPD in two large sample studies, variables that may account for the AHI suppressor effects and the need for testing more complex interactive predictive models of harsh parenting behaviors are discussed.